PROSES PEMBUATAN PIPA INLET PADA PEMANAS AIR TENAGA SURYA (SOLAR WATER HEATER) MENGGUNAKAN MESIN CNC - muhibbin, iwan alif; Pewiranegara, Agus Alamsyah (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Abstract Solar water heaters first appeared in the late 1800s in California, United States, By Clarence M Kemp The vitial concept of a solar water heater, which was first made by Kemp, is 3 tanks which are inputted with water and then heated into thetank, several components contained in the Solar Water heater are, Collector, Tank, Anode, Electric backup, Inlet pipe, Temperature- Pressure Relief Valve & Vacuum Valve Of the several components, the inlet pipe is one of the most important components for distributing materials such as liquids, gases, and steam, from the reservoir to the pump house The development of a pipe from one of the Manufacturers of PT Steel Pipe Industry of Indonesia Tbk (ISSP) stated that For now, the pipeline is quite optimistic that it can achieve its sales target. ISSP Corporate Secretary and Investor Relations, Johanes W. Edward said the company'snet profit until December 2021 is targeted to reach Rp490 billion. According to Ahmad Fauzi et al. (2021), and Zubaidi, et al (2012-40) state that a machine is needed that is able to meet all the demands in the manufacturing industry, one of which is a CNC machine, a type of machine tool that uses a control system with commands in the form of a numeric code used to control these machine tools, and the advantages of CNC lathes compared to conventional lathes are more effectiveand efficient (Elvys & Arisandi, 2017 239) Then Zubaidi, et al (2012 40) Before the process of making the Inlate Pipe, the design drawing stage was carried outusing solidwork software, material cutting, inspection, making CNC programs, and turning processes. The process of making one inlate pipe takes 6.67 minutes. The process of making program code using CNC Simulator manually, before creating program code, you at first know the symbols such as G code, M code, andsupporting code (O. N. X. 1. 2). Pay attention to the size of the working drawing when making program code After that, the process of setting the sero point on the CNC lathe